Earthquake-altered flooding hazard induced by damage to storm water systems. Issue 1 (10th June 2016) - Cavalieri, Francesco; Franchin, Paolo; Giovinazzi, Sonia
Abstract: Major earthquakes can cause extensive transformations to the land underlying cities, leading to decreased capacity in natural and built drainage systems and, as a consequence, to Increased Flooding Hazard (IFH). This phenomenon causes some areas, which previously were not exposed to flooding, to have the potential to flood, and already flood-prone areas to likely experience increased flood depth during the next rainfall events. This scenario occurred in Christchurch city, New Zealand, after the 2010–2011 Canterbury Earthquake Sequence (CES). The IFH was observed in many urban areas during a series of rainfall events occurred in the years after the CES. This paper proposes a method for analysing and assessing to what extent the earthquake-induced damage to storm water pipelines and the consequent impacts on the connectivity and capacity levels of the pipeline storm water network could contribute to the IFH. A probabilistic analysis, through a Monte Carlo simulation, is suggested for the proposed method so that the uncertainty affecting several key parameters can be accounted for. The proposed probabilistic method for IFH was implemented as an additional module within a recently developed open-source simulation tool, OOFIMS. Results from the added OOFIMS module are presented in terms of maps and cumulative distribution functions of increased flood height and flooded area, impact metrics that can be useful for emergency managers and infrastructure owners. The effectiveness of the proposed method to assess earthquake-altered flooding hazard and the relative OOFIMS-added module are tested using Christchurch as a case-study.